Evolution of standardization of therapeutic and diagnostic allergens produced in Russia - S. S. Masalskiy; E. I. Sakanyan; M. A. Yasnaya (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Allergen-specific immunotherapy is based on the development of induced tolerance in patients. Natural extracts are most often used as therapeutic allergens worldwide.The article presents new approaches to biological standardization of subcutaneous administered allergens. It is established that own standard allergens have specific allergenic activity, which was determined on sensitized patients-volunteers. The Russian Federation uses its own units - EAA (Units of Allergenic Activity). 100 000 EAA/mL corresponds to the size of wheal in prick test equal to 8 mm. The internal reference material (RM) of allergenic activity of pollen allergens "Microgen" have different specific activity depending on the type of allergen. The most common series have allergenic (specific) activity in the range of 150,000 - 200,000 EAA/mL.The control of the specific activity of allergen drugs is carried out in accordance with the current certified standard samples of the company's standards. A method of competitive enzyme-linked immunosorbent assay using specific sera containing specific IgE antibodies is used for this purpose.In addition, the specific activity of allergen preparations is certified through three additional characteristics: total protein content (using the Bradford method), protein profile (through electrophoresis in a polyacrylamide gel with sodium dodecyl sulfate under reducing conditions), and authenticity through the presence of major specific components, which is determined by the Western blot method using sera containing IgE antibodies specific for the corresponding allergen.Currently, in the Russian Federation, the standardization of therapeutic and diagnostic allergens is conducted simultaneously according to two indicators: protein nitrogen content, expressed in Protein Nitrogen Units (PNU), and allergenic (specific) activity expressed in units of allergenic activity per milliliter (EAA/ml). While the PNU indicator partially reflects the allergenic properties of the drug, it does not fully capture these properties, making it necessary to remove PNU from the list of quality indicators for allergen medicines. This would require changes to regulatory documentation and instructions for allergens.When evaluating the allergenic activity of allergens, it is now recommended to focus on units of EAA. The consistency of the protein composition and presentation in the drug ensures increased safety and efficacy of therapy, as well as allows for comparison between drugs.